Investigator's Guide to Steganography - Kipper, Gregory (CRC Press, 2009)
Investigators within the law enforcement and cyber forensics communities are generally aware of the concept of steganography, but their levels of expertise vary dramatically depending upon the incidents and cases that they have been exposed to. Now there is a book that balances the playing field in terms of awareness, and serves as a valuable reference source for the tools and techniques of steganography.